PEMODELAN DATA GRAVITASI DENGAN MENGGUNAKAN METODE POLIGON TALWANI 2D - Prasetyo, Adi
Gravity is one of exploration techniques in exploration geophysics. Generally, the gravity technique is used for the initial phase of exploration, because the gravity is very efficient for the overall mapping anomalies in the wide area. The principle of Gravity is using attraction of gravity between gravity meter with a mass below the surface of the earth, and very dependent on the variation of the density of earth material beneath the surface. One of the gravity data interpretation technique is use the polygon talwani method. This method uses the principles integral around a closed object of a polygon n-side. This method can be considered to interpret the form of material accurately. In this final duty report, described the potential for modeling and interpretation of coal using polygon talwani method 2-D. After interpret using the polygon talwani method 2-D, resulting gravity anomalies caused by coal mining (Anthracite, solid) with density 1.4 g/cm3. Once calculated, the potential of coal is about 700 million tons of coal.